Choreographing problems : expressive concepts in contemporary dance and performance. - Cvejić, Bojana (Basingstoke : Palgrave, 2015)
This book illuminates the relationship between philosophy and experimental choreographic practice today in the works of leading European choreographers. A discussion of key issues in contemporary performance from the viewpoint of Deleuze, Spinoza and Bergson is accompanied by intricate analyses of seven groundbreaking dance performances.
Introduction 1. Problems and Expressive Concepts 2. Disjunctive Captures of the Body and Movement 3. Theatrical Apparatuses of Disjunction 4. Exhausting Improvisation: 'Stutterances' 5. A Critical Departure from Emotionalism: Sensations and Affects in the Mode of Performing 6. During and After Performance: Processes, Caesuras and Resonances Conclusion Bibliography Index
boek